PENGARUH SYSTEMATIC APPROACH TO PROBLEM SOLVING TERHADAP KEMAMPUAN PEMECAHAN MASALAH PADA MATERI PERHITUNGAN KIMIA - Heni Wulandari; Husna Amalya Melati; Rahmat Rasmawan (Universitas Tanjungpura, 2019)
AbstractThe study aimed to determine the effect of systematic approach to problem solving on students’ problem solving ability on chemical calculation material at SMAN 1 Tebas. The form of this study was pre exprimental design with one group pretest posttest design. As many as 20 students of X grade MIA 2 as sample which was selected by purposive sampling technique. Data in this study were obtained from the result of pretest and posttest. The result showed that the percentage of students’ problem solving ability were on pretest and posttest were 22.17% (less category) and posttest 72.66% (good category) respectively. The Wilcoxon test result showed that there was a difference in problem solving ability before and after treatment. The result improved on medium category with N-Gain score 0.67. This study was expected to be an alternative learning for students to improve the problem solving ability in solving problems.Keywords: Chemical calculation, Problem solving ability, Systematic approaach to problem solving